Prevalence of depression and anxiety symptoms and their determinant factors among patients with cancer in southern Ethiopia: a cross-sectional study. Issue 1 (21st January 2022) - Ayalew, Mohammed; Deribe, Bedilu; Duko, Bereket; Geleta, Dereje; Bogale, Netsanet; Gemechu, Lalisa; Gebretsadik, Achamyelesh; Bedaso, Asres
Abstract : Objective: The study was aimed to assess the prevalence of depression and anxiety symptoms and their determinant factors among patients with cancer attending follow-up at Hawassa University Comprehensive Specialized Hospital cancer treatment centre, Ethiopia. Design: Institution-based cross-sectional study design was implemented. Setting: Patients with cancer at Hawassa University Comprehensive Specialized Hospital cancer treatment centre from October 2019 to December 2019. Participants: Randomly selected 415 patients with cancer who had follow-up at cancer treatment centre. Main outcome measures: Anxiety and depression symptoms were assessed using Hospital Anxiety and Depression Scale. Result: The prevalence rates of depression and anxiety symptoms were found to be 244 (58.8%) and 249 (60.0%), respectively. Older age (>50 years) (AOR (adjusted OR)=2.24, 95% CI=1.14 to 4.40), being unemployed (AOR=1.96, 95% CI=1.08 to 3.56), advanced stage of cancer such as stage III (AOR=5.37, 95% CI=1.34 to 21.45) and stage IV (AOR=4.55, 95% CI=1.12 to 18.44), comorbid psychotic symptoms (AOR=1.67, 95% CI=1.07 to 2.61) and eating problem in the past 2 weeks (AOR=6.16, 95% CI=1.98 to 19.11) were independent factors significantly associated with depressive symptoms. In addition, cancer stage such as stage II (AOR=3.92, 95% CI=1.07 to 14.36) and stage IV (AOR=5.04, 95% CI=1.44 to 17.59) and comorbid psychotic symptoms (AOR=1.73, 95% CI=1.12 to 2.66) were significantly associated with anxiety symptoms. Conclusion: Depression and anxiety symptoms among patients with cancer were considerably high. Age, occupation, cancer stage, comorbid psychotic symptoms and eating problem were determinant factors of depressive symptoms among patients with cancer. Moreover, cancer stage and comorbid psychosis were determinants of anxiety symptoms. Healthcare professionals working in the oncology unity need to conduct routine screening and treatment of depression and anxiety symptoms for patients with cancer.